Cytokine indicator of the oral cavity - a new index in the diagnosis of dental diseases - M. I. Kuzmin; V. J. Lukashov; G. G. Sveshnikov; A. N. Bondarenko (Кубанский научный медицинский вестник, 2014)
On the basis of the study, 20 patients with chronic generalized periodontitis of moderate severity, 20 patients with single fractures in the body of the mandible and 20 volunteers with intact periodontium developed a new immunological indicator to differentiate between acute dental process from chronic and very dynamics of transformation, which adequately reflects the seriousness of the disease and effectiveness of treatment.